Coronavirus Disease 2019 Outbreak in a San Francisco Homeless Shelter. (3rd August 2020) - Imbert, Elizabeth; Kinley, Patrick M; Scarborough, Ashley; Cawley, Caroline; Sankaran, Madeline; Cox, Sarah N; Kushel, Margot; Stoltey, Juliet; Cohen, Stephanie; Fuchs, Jonathan D
Abstract: We report the public health response to a coronavirus disease 2019 (COVID-19) outbreak in a San Francisco shelter where 67% of residents and 17% of staff tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We describe the limited utility of case investigation, person-based contact tracing and symptom screening, and the benefits of mass testing in outbreak response.